Vitamin D and Bone Metabolism in Celiac Disease. The Possibilities of Dietary Correction - Anatoly I. Khavkin; Valeriya P. Novikova; Elena I. Kondratyeva; Elena V. Loshkova; Galina N. Yankina (Педиатрическая фармакология)
The review describes the state of the vitamin D system and bone metabolism in celiac disease, the mechanisms of the influence of vitamin D on the state of the intestinal mucosa, and risk factors that contribute to pathological changes in bones in celiac disease. Studies are presented that evaluate bone mineral density, bone metabolism, and vitamin D status in patients with celiac disease. The results of a discussion on the effect of calcium and vitamin D supplements on the course of celiac disease and the condition of bone tissue in this disease are presented.